2004
DOI: 10.1097/01.ccm.0000147770.20400.10
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, prospective trial of oxygen, continuous positive airway pressure, and bilevel positive airway pressure by face mask in acute cardiogenic pulmonary edema*

Abstract: Compared with oxygen therapy, CPAP and bilevel-PAP resulted in similar vital signs and arterial blood gases and a lower rate of endotracheal intubation. No cardiac ischemic complications were associated with either of the noninvasive ventilation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
116
0
23

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(155 citation statements)
references
References 27 publications
16
116
0
23
Order By: Relevance
“…This result compares favourably with the study by Kosowsky et al, reporting an in hospital intubation rate of 7 out of 19 (37%). Intubation rate and overall mortality of the present study is in line with recent reports on the in-hospital [4,[7][8][9][10]27] and out-hospital [12] application of CPAP and Pressure Support Ventilation in ACPE. Oxygen saturation improved, respiratory rate, heart rate, and blood pressure decreased in both groups.…”
Section: Efficacy Of Helmet Cpapsupporting
confidence: 80%
See 2 more Smart Citations
“…This result compares favourably with the study by Kosowsky et al, reporting an in hospital intubation rate of 7 out of 19 (37%). Intubation rate and overall mortality of the present study is in line with recent reports on the in-hospital [4,[7][8][9][10]27] and out-hospital [12] application of CPAP and Pressure Support Ventilation in ACPE. Oxygen saturation improved, respiratory rate, heart rate, and blood pressure decreased in both groups.…”
Section: Efficacy Of Helmet Cpapsupporting
confidence: 80%
“…[2][3][4][5][6][7][8][9][10]. Despite this background, reports of CPAP application in prehospital setting are, to our knowledge quite limited.…”
Section: Out Of Hospital Use Of Cpapmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent randomized study, Bellone et al [26], however, concluded that CPAP and NIPPSV were equivalent in terms of clinical parameters improvement, but also in terms of myocardial infarction rate or troponin plasma levels increase. In all subsequent clinical comparisons, both CPAP and NIPPSV proved superior to medical therapy alone in terms of reducing the intubation rate [27,28], without any adverse event rate or outcome differences.…”
mentioning
confidence: 92%
“…Over the past three decades, application of noninvasive ventilation (NIV) either with continuous positive airway pressure (CPAP) or Bi-level positive airway pressure (Bi-PAP) has been used with the standardized medical treatment as an effective therapeutic approach to treat ACPE [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%